Contabilidade e direito tributário - do fato (jurídico) contábil ao fato jurídico tributário - : a construção da renda tributável - Martins, Natanael (2012)
The purpose of this study is to establish a connection between accounting and Law, aiming at the investigation of how accounting recognizes the facts as accounting events, and how, pursuant to tax rules, such facts are recorded as accounting events of a tax nature to determine the taxable income. In order to do so, initially we interpreted the subject in the context of the Federal Constitution, by underlying the principles of income tax and, especially the constitutional meaning of income. We analyzed the origins, concepts and theories of accounting, by examining its basic rules and showing that accounting is also Law, and therefore the current discussions regarding whether Accountancy would be Law, especially in connection with Tax Law, sound pointless. The comprehension of Accountancy language is essential, since the taxable events derive from the accounting entries made in the financial statements based on the taxation rules instead of accounting rules, whether determining the mere conversion of an accounting event into a tax accounting event or imposing a particular criterion to recognize such event, regardless the fact that both events are deemed as legal facts. We also analyzed the assumptions of the so-called new accounting rules , aiming at demonstrating that, contrary to the so-called old accounting rules , the basics of the new accounting rules resides in the financial evaluations rather than in the profit effectively realized, so that the profit recognized under the new accounting rules is not necessarily the profit entirely realized. In purpose of our investigation, we researched the composition of the taxable real profit, demonstrating that, provided that the constitutional concept of income prevails, the legislator may qualify the taxable real profit, imposing conditions, for instance, in connection with deductible costs and expenses, once the income tax levies on the realized income, and not on the income occasionally earned by the taxpayer. Finally, we aim at demonstrating that for purposes of income tax, the Federal Constitution rules require that the taxable income is effectively realized; otherwise it would violate principles of legal certainty, the ability to pay, and non-confiscation